Licenciatura em Matemática na modalidade a distância do Instituto Federal do Triângulo Mineiro : entre o pensado e o realizado - Silva, Suselaine da Fonseca (2015)
This work was developed based on research carried out on the deployment of Mathematics Degree course Distance of the Federal Institute of Miner Triangle. The study aimed to discuss the contribution of the deployment parameters and development of this course in distance teacher training that already operate or will operate in Basic Education. Among the objectives set out in this study, we sought to understand the concept of education that guides the pedagogical project of implementation of that course, delineating the profile of the student and the other agents involved in the teaching and learning process, and also analyze the process of formation which is being developed during the course and its practical implication in the constitution of teaching. The theoretical lens used to support this research are theories of Papert (2008) on the constructionist approach and the instructional approach in the use of technology for learning and Freire (2004) considerations with respect to the contrast of banking education to liberating education, attempting to understand the process of idealization and development, in deployment of the course in question. We also take as a basis the ideas of Moore andKearsley (2007) and Belloni (1999), to support distance education as a viable possibility for learning.The researchmethodologyis qualitative - exploratory and descriptive - focusing produced the kind of training in accordance with the established parameters. The instruments used in the research include document analysis, interviews and questionnaires, and data collected in the own virtual learning environment. After analysis, it was found that the deployment parameters of the course are consistent with the constructionist approach proposed by Papert (2008) and the liberating education defendedby Freire (2004) in orderto fully prepare students as responsible for their own learning. In this, it is possible for him to develop autonomy and creativity, as the teacher or tutor behaves as a mediator of learning. However, the results also showed that the proposed activities on the environment by the teachers and the way how courses are conducted not always consistent with this parameter and is necessary to review the adopted methodological process, prioritizing the construction of knowledge by students and contextualization of Mathematics in a practical and dynamic way.